Biology and Management of the New Zealand Endemic Wheat Bug, Nysius huttoni (Hemiptera: Lygaeidae). (17th November 2019) - Tiwari, Sundar; Wratten, Steve D
Abstract: The wheat bug, Nysius huttoni White, mainly reported as a pest of wheat and forage brassicas, is native to New Zealand. This pest has been accidentally introduced into The Netherland and Belgium during apple exports from New Zealand. The bug population is abundant in open sparse vegetations and hot-dry habitats, and feeds on dropping seeds. It damages wheat grains during milk-ripe stage by piercing through the glumes into the developing grains that can reduce gluten protein and reduce baking quality. Bugs also suck phloem fluid from seedlings, which can reduce plant establishment in forage brassicas. Early scouting and field monitoring are suggested before making pest management decisions. Seed treatment with neonicotinoids, permethrin, and chlorpyrifos spray in the standing crops are chemical methods of management in New Zealand. These conventional synthetic pesticides have nontarget effects on human health, the environment, and biodiversity. However, preventive measures such as the use of less-susceptible cultivars, and using potential trap crops is other important pest management options. Alyssum ( Lobularia maritima L. Desv. Brassicales: Brassicaceae) and wheat ( Triticum aestivum L. Poales: Poaceae) are two potential trap crops of wheat bug. Kale ( Brassica oleracea L.) cultivars, such as Corka and Regal, and wheat ( Triticum aestivum ) cultivars, such as Batten, Domino, and Oroua, are less-susceptible cultivars. Understanding the biology and ecology of the pest, and utilizing preventative pest management measures such as the use of trap crops and less-susceptible cultivars, and integrating these with 'soft' chemicals make a suitable integrated pest management strategy for this pest.